Bounds on neutrino-DM interactions from TXS 0506+056 neutrino outburst - Zapata, Gabriel D.; Jones-Pérez, Joel; Gago, Alberto M. (IOPscience, 2025)
We constrain the neutrino-dark matter cross-section using the 13±5 neutrino event excess observed by IceCube in 2014-2015 from the direction of the blazar TXS 0506+056. Our analysis takes advantage of the dark matter overdensity spike surrounding the supermassive black hole at the center of the blazar. In our results, we take into account uncertainties related to the different types of neutrino emission models and the features of the dark matter spike, considering cross-sections that scale with energy as σ (Eν/E0)n, for values of n = 1, 0, -1, -2. In our best-case scenario, we obtain limits competitive with those derived from other active galaxies, tidal disruption events (TDEs), and the IC-170922A event.

Restringimos la sección eficaz de interacción neutrino–materia oscura utilizando el exceso de 13±5 eventos de neutrinos observado por IceCube en 2014–2015 desde la dirección del blazar TXS 0506+056. Nuestro análisis aprovecha la presencia de un pico de sobredensidad de materia oscura que rodea al agujero negro supermasivo en el centro del blazar. En nuestros resultados, tomamos en cuenta las incertidumbres asociadas a los diferentes modelos de emisión de neutrinos y a las características del spike de materia oscura, considerando secciones eficaces que escalan con la energía como σ∝(E0/Eν)^n, para valores de n=1,0,−1,−2. En nuestro mejor escenario, obtenemos límites competitivos con los derivados de otras galaxias activas, de eventos de disrupción por marea (TDEs), y del evento IC-170922A.
Keywords: Neutrinos; Materia oscura (Astronomía); Agujeros negros (Astronomía); https://purl.org/pe-repo/ocde/ford#1.03.00